Power Stroke Angular Velocity Profiles of Archaeal A-ATP Synthase Versus Thermophilic and Mesophilic F-ATP Synthase Molecular Motors - Sielaff, Hendrik (2017)
The angular velocities of ATPase-dependent power strokes as a function of the rotational position for the A-type molecular motor A3B3DF, from the Methanosarcina mazei Gö1 A-ATP synthase, and the thermophilic motor α3β3γ, from Geobacillus stearothermophilus (formerly known as Bacillus PS3) F-ATP synthase, are resolved at 5 μs resolution for the first time. Unexpectedly, the angular velocity profile of the A-type was closely similar in the angular positions of accelerations and decelerations to the profiles of the evolutionarily distant F-type motors of thermophilic and mesophilic origins, and they differ only in the magnitude of their velocities. M. mazei A3B3DF power strokes occurred in 120° steps at saturating ATP concentrations like the F-type motors. However, because ATP-binding dwells did not interrupt the 120° steps at limiting ATP, ATP binding to A3B3DF must occur during the catalytic dwell. Elevated concentrations of ADP did not increase dwells occurring 40° after the catalytic dwell. In F-type motors, elevated ADP induces dwells 40° after the catalytic dwell and slows the overall velocity. The similarities in these power stroke profiles are consistent with a common rotational mechanism for A-type and F-type rotary motors, in which the angular velocity is limited by the rotary position at which ATP binding occurs and by the drag imposed on the axle as it rotates within the ring of stator subunits.